2018
DOI: 10.1172/jci.insight.121225
|View full text |Cite
|
Sign up to set email alerts
|

Calpain-6 controls the fate of sarcoma stem cells by promoting autophagy and preventing senescence

Abstract: Sarcomas are still unsolved therapeutic challenges. Cancer stem cells are believed to contribute to sarcoma development, but lack of specific markers prevents their characterization and targeting. Here, we show that calpain-6 expression is associated with cancer stem cell features. In mouse models of bone sarcoma, calpain-6-expressing cells have unique tumor-initiating and metastatic capacities. Calpain-6 levels are especially high in tumors that have been successfully propagated in mouse to establish patient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…A nonclassical calpain demonstrated a different effect regarding the control of the autophagy system in sarcoma cells. Knockdown of calpain-6, which is strongly upregulated in cells with tumor-initiating and metastatic capacities, suppressed autophagy as well as hypoxia-dependent prevention of senescence entry [160, 161]. The Kaposi sarcoma-associated herpesvirus inhibits autophagy and impairs monocyte differentiation into dendritic cells as an immune evasion strategy, by reducing CAST expression and consequently leading to decreased ATG5 levels [162].…”
Section: Calpains and Autophagy In Neurodegeneration And Other Medmentioning
confidence: 99%
See 1 more Smart Citation
“…A nonclassical calpain demonstrated a different effect regarding the control of the autophagy system in sarcoma cells. Knockdown of calpain-6, which is strongly upregulated in cells with tumor-initiating and metastatic capacities, suppressed autophagy as well as hypoxia-dependent prevention of senescence entry [160, 161]. The Kaposi sarcoma-associated herpesvirus inhibits autophagy and impairs monocyte differentiation into dendritic cells as an immune evasion strategy, by reducing CAST expression and consequently leading to decreased ATG5 levels [162].…”
Section: Calpains and Autophagy In Neurodegeneration And Other Medmentioning
confidence: 99%
“…Moreover, the intravitreal injection of siRNA directed against CSS1 reduced calpain activation and beclin-1 cleavage in an in vivo model for retinal ischemic injuries [136]. In a mouse model for bone sarcoma, knockdown of the nonclassical calpain-6 blocked tumor development, and overexpression of this protease in an osteosarcoma cell line increased autophagic flux, which could rather favor tumorigenesis [161].…”
Section: Calpains and Autophagy In Neurodegeneration And Other Medmentioning
confidence: 99%
“…Tumor cyto-chemical resistance is associated with the activation of the NF-κB, Ras/MAPK and PI3K/AKT pathways ( 62 , 63 ), further demonstrating the association between CAPN6 expression and osteosarcoma cell chemical resistance. In addition, in liposarcoma, it has been found that the higher the tumor grade, the higher the CAPN6 expression ( 64 ), indicating that the expression of CAPN6 is associated with the malignancy of sarcoma.…”
Section: Capn6 In Tumorsmentioning
confidence: 99%
“…Hypoxia can also activate NF-κB and increase the expression of EDN-1 receptors, thereby promoting the EDN-1/NF-κB pathway to induce increased mRNA and protein levels of CAPN6, resulting in a marked decrease in the silencing of Oct4, Nanog or Sox2 ( 68 ). In a previous study, in an osteosarcoma mouse model, it was found that cells expressing CAPN6 had unique tumor initiation and metastasis capabilities; CAPN6 knockdown inhibited hypoxia, promoted autophagy, prevented aging, induced cancer stem cell population depletion and blocked mouse tumor development ( 64 ). CAPN6 expression also recognizes CSCs.…”
Section: Capn6 In Tumorsmentioning
confidence: 99%
“…Autophagy deficiency in the CD271+ cells decreased the stemness marker expression, restored chemotherapeutics sensitivity and restricted the advantage of CD271+ OS cells in terms of tumorigenesis in vivo [79]. More recently, calpain-6 was demonstrated to control OS CSC fate by promoting autophagy and preventing senescence [80].…”
Section: Autophagy In Osteosarcomamentioning
confidence: 99%